(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
The adaptation of science to human needs is technology. Technology the current technological developments are accelerating to the point that they can permanently harm our planet. Every technology has advantages and disadvantages, but they prefer to ignore the bad effects that are producing major disruptions in human life and animal habitats. As a result, green technology aims to protect the environment through the use of never-ending natural energy. It also serves to minimize the effects of atmospheric pollutant emissions by replacing trash with renovated goods, which leads to greenery and greening. There are just a few divisions. They all have no adverse effects and will thus be learned by future generations. It is only because we damage this world that we are accountable for rescuing. In addition to the green technological advantages, this study shows value. Over 100 billion was invested in 2007, setting new global records for new renewable energy resources, industrial plants and research & development. However, since renewable energy aspirations fall behind practice due to the rapid rate of transformation in recent years.